암예방법 정보에 대한 인지된 모호성과 인지된 암위험 및 암예방행동과의 관련성 - 계수연(Su Yeon Kye) (보건교육건강증진학회지, 2018)
Objectives: This study aims to examine associations between the perceived ambiguity about cancer prevention recommendations with perceived cancer risk and cancer prevention behaviors. Methods: Participants for this study were 1,000 men and women aged 20-69 years. We performed logistic regression analyses to test the effects of ambiguity on perceived cancer risk and cancer prevention behaviors. Results: Perceived ambiguity was positively related with perceived cancer risk and drinking, and was inversely associated with consumption of fruits and vegetables and avoiding salty or burnt foods. Conclusions: These findings suggest that perceived ambiguity about cancer prevention recommendations may have broad and important effects on other health cognitions and behaviors, and we discuss the implications of these findings for future cancer communication efforts. KCI Citation Count: 0